Eksistensi Lembaga International Monetary Fund, World Bank, dan International Labour Organization Sebagai Organisasi Ekonomi Internasional - Muhammad Rafi Darajati (Kyadiren, 2020)
As one of the international law subjects, international organizations play an important role in the international economy. International economic law does not only discuss the rules of law through international agreements and principles, but also regulates the functions and authorities of international economic organizations that have been recognized as subjects of international law. Among these international organizations are the IMF, World Bank, and the ILO. This article aims to discuss the existence of the IMF, World Bank, and ILO in the field of international economic law. The IMF and World Bank are more engaged in helping countries experience serious economic difficulties, while the ILO is more focused on labor issues.